Intercomparison of middle atmospheric meteorological analyses for the Northern Hemisphere winter 2009–2010 - J. P. McCormack (Copernicus Publications, 2021)
Detailed meteorological analyses based on observations extending through the middle atmosphere (∼ 15 to 100 km altitude) can provide key information to whole atmosphere modeling systems regarding the physical mechanisms linking day-to-day changes in ionospheric electron density to meteorological variability near the Earth's surface. However, the extent to which independent middle atmosphere analyses differ in their representation of wave-induced coupling to the ionosphere is unclear. To begin to address this issue, we present the first intercomparison among four such analyses, JAGUAR-DAS, MERRA-2, NAVGEM-HA, and WACCMX+DART, focusing on the Northern Hemisphere (NH) 2009–2010 winter, which includes a major sudden stratospheric warming (SSW). This intercomparison examines the altitude, latitude, and time dependences of zonal mean zonal winds and temperatures among these four analyses over the 1 December 2009 to 31 March 2010 period, as well as latitude and altitude dependences of monthly mean amplitudes of the diurnal and semidiurnal migrating solar tides, the eastward-propagating diurnal zonal wave number 3 nonmigrating tide, and traveling planetary waves associated with the quasi-5 d and quasi-2 d Rossby modes. Our results show generally good agreement among the four analyses up to the stratopause (∼ 50 km altitude). Large discrepancies begin to emerge in the mesosphere and lower thermosphere owing to (1) differences in the types of satellite data assimilated by each system and (2) differences in the details of the global atmospheric models used by each analysis system. The results of this intercomparison provide initial estimates of uncertainty in analyses commonly used to constrain middle atmospheric meteorological variability in whole atmosphere model simulations.